Efficiency analysis of zakat organization in national level and region of Semarang city - Nafisatul Firdaus; Nur Ichsan; Atieq Amjadallah (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2019)
This study aims to determine the level of efficiency of Zakat Management Organization at National Level and Regional Level Semarang relaif by using Data Envelopment Analysis method with production approach. This method measures the ratio between output and inputs comparing OPZ National Level on 2010-2015 period examined, and comparison between OPZ Semarang City and National Level in 2015. The results shows the comparison of efficiency between zakat institution at national level and regional level of Semarang City in 2015, that means zakat institution at Semarang City level is as efficient as zakat institution at national level in 2015.